The electrolyte abnormalities and duration of hospitalisation in children with gastroenteritis - Zehra, Vaseefat Ul; Mir, Naseer Yousuf; Memar, Elmira Haji Esmail; Fayaz, Aakifa (International Journal of Contemporary Pediatrics, 2022)
Background: Diarrhoea remains one of the major causes of death among infants significantly in Asia, Africa and Latin America. The major contributing factors for higher incidence and mortality rates are improper sanitation, unsafe drinking water, physiological conditions like malnutrition, weak immune system.Rotavirus is the major causative agent of diarrhoea in young children in developed and undeveloped countries. Electrolyte abnormalities is the leading causes of morbidity and mortality in younger children with acute gastroenteritis and increased mortality is seen in malnourished children. The common abnormalities associated with acute gastroenteritis are hyponatremia and hypokalaemia. The average duration of hospital stay is 2.5 days. Methods: This is a descriptive cross-sectional study which studied 173 patients of acute gastroenteritis which have been admitted to the CMC, Tehran in 1 year. (June 2021-May2022). Results: In this study 173 patients were studied. 101 patients (58.4%) were infants, 55 patients (31.8%) were preschool children and 17 patients (9.8%) were older children. 70 patients (40.5%) were females and 103 patients (59.5%) were males. The most common electrolyte abnormality that was encountered in this study is hyponatremia (51.4%) >hypokalaemia (11.6%) >hypernatremia (6.9%) >hyperkalaemia (1.2%). Conclusions: The order of electrolyte abnormalities seen: Hyponatremia (51.4%), hypokalaemia (11.6%), hypernatremia (6.9%), hyperkalaemia (1.2%). Duration of hospitalisation is 1 day for majority of the patients and is high for patients with hyponatremia.